Multivariate analysis in the development of bioequivalent tablets containing bicalutamide - Goněc, Roman; Franc, Aleš; Doležel, Petr; Farkaš, Pavel; Sova, Petr (Pharmaceutical development and technology, 2021)
The pharmaceutical industry has to tackle the explosion of high amounts of poorly soluble APIs. This phenomenon leads to numerous sophisticated solutions. These include the use of multifactorial data analysis identifying correlations between the components and dosage form properties, laboratory and production process parameters with respect to the API liberation Example of such API is bicalutamide. Improved liberation is achieved by particle size reduction. Laboratory batches, with different PSD of API, were filled into gelatinous capsules and consequently granulated for tablet compression. Comparative dissolution profiles with Casodex 150 mg (Astra Zeneca) were performed. The component analysis was used for the statistical evaluation of f1 and f2 factors and D(v,0.9) and D[4,3] parameters of PSD to identify optimal PSD values. Suitable PSD limits for API were statistically confirmed in laboratory and in commercial scale with respect to optimized tablet properties. The tablets were bioequivalent with originator (n = 20; 90% CI for ln AUC0-120: 99.8-111.9%; 90% CI for ln cmax: 101.1-112.9%). In conclusion, the micronisation of the API is still an efficient and inexpensive method improving the bioavailability, although there are more complicated and expensive methods available. Statistical multifactorial methods improved the safety and reproducibility of production.
Keywords: Chemistry, Pharmaceutical; Tosyl Compounds; nitrily; Multivariate Analysis; Tablets; biologická dostupnost; tablety; terapeutická ekvivalence; multivariační analýza; Nitriles; Therapeutic Equivalency; tosylové sloučeniny; anilidy; Biological Availability; farmaceutická chemie; Anilides